Pembuatan Indeks Subjek Tugas Akhir Mahasiswa D4 dari Tahun 2013-2017 di Perpustakaan Politeknik Negeri Padang - Ayu, Feby; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
This paper is to describe the way of making Index from final assignment of D4 students from 2013-2017 in theLibrary of State Polytechnic of Padang. Data was collected by direct observation in theLibrary of State Polytechnic of Padang. Data analysis is done descriptively. Based on the result of the discussion of making the title index of final assignment of D4 students in State Polytechnic of Padang can be concluded through several stages as follows: (1) initial observation of the document that is observing the documents to be indexed and make details about the document; (2) determine the main subject that is in making an index required determination of the main subject then in this paper which became the main subject in making this index is the title index of final assignment of D4 student from year 2013-2017 in State Polytechnic of Padang; (3) create a description of the index describing the subjects to be indexed; (4) the terms in which indexing should be included in accordance with the data obtained without altering it; (5) indexing languages using clear and precise language; (6) create a subject index that is divided from several parts, namely authorship writing and title determination; (7) and typing of the index and examination of the index that has been typed in order to avoid error.iKeyword : index, final assignment.